Genetic Variation in Cardiac Troponin T Gene TNNT2 in Iraqi Patients with Cardiomyopathy - Majida H. Mutlag, Jabbar H. Yenzeel, Mahmood R. Subhi, (Pakistan Journal of Medical & Health Sciences, 2022)
Cardiomyopathy is an affliction of the heart muscle that can result in heart failure.It comes in a variety of phenotypes, such as dilated, hypertrophic, and restricted. This study was aimed to investigate the polymorphism in cardiac Troponin T gene TNNT2 in Iraqi patients with cardiomyopathy. Eighty-two diagnosed cardiomyopathy adult patients with age range between (20-70) years, and thirty healthy with same range, were involved in this study during their attendance at Ibn Al- Bitar Center for Cardiac Surgery. The patients were diagnosed by an expert cardiologists based on ECG changes, Echocardiogram, chest x ray. The study was conducted from October 2020 to March 2021, and approved by ethical committees.: CSEC/0920/0052, September 15, 2020 of department of Biology, College of Science, University of Baghdad. Sequencing of the PCR products was performed by the genetic analyzer for forward and reverse primers in macrogen company (South korea), to detect the polymorphism in TNNT2 gene in cardiomyopathy patients. DNA was isolated from both groups (patients and control), and amplification of TNNT2 by using new set of primers to amplify 443 bp from (rs74315380, rs74315379) SNPs and 351bp from (rs3729547) SNP for being use in sequencing portion, and target SNPs will be involved in this region. The genotypes frequency of the rs3729547 SNP showed highly significant (p<0.001) different between patients and healthy group. Similarity, there is significant (p<0.05) differences among CC, TC and TT genotypes according to patients and healthy individuals. The SNP rs3729547 genotypes frequency in dilated cardiomyopathy (DCM) and hypertrophic cardiomyopathy (HCM) showed significant (p<0.05) different between DCM and HCM patients related to TT genotypes, but not for CC and TC genotypes. Similarity, there is significant (p<0.05) different among CC, CT and TT genotypes according to DCM and HCM patients.